Analisis Kuat Beton Geopolimer Menggunakan Fly Ash dan Abu Sekam Padi - Ika Sulianti; Indrayani -; Agus Subrianto; Efrilia Rahmadona; Oktri Yanti; Arista Widya Iryani (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2021)
One of concrete construction development is the use of geopolymer concrete which is environmentally friendly and efficient in regard to energy utilization. In this study, four combinations of fly ash (FA) and rice husk ash (RHA) was used, namely: i) 100% FA and 0% RHA, ii) 75% FA and 25% RHA, iii) 50% FA and 50% RHA, and iv) 25% FA and 75% RHA, with addition of alkaline solution mix of Na2SiO3 and NaOH with a ratio of 5:1 at 7 days, 14 days, and 28 days of concrete age, with cube samples and will be done a compressive strength test of 225 kg/cm2 (28 days of concrete age). This study aims to determine the optimum variation and analyze the compressive strength of geopolymer concrete using FA and RHA with the addition of an alkaline solution of Na2SiO3: NaOH = 5: 1. Results found that the optimum variation was in the geopolymer concrete mix of 100% FA and 0% RHA with a compressive strength value of 395.643 kg/cm2 (28 days of concrete age), whereas other variations have shown a decrease of compressive strength compare to the normal concrete. Therefore, the geopolymer concrete variation of 100% FA and 0% RHA has a higher compressive strength because the cement substitute used (100% fly ash) contains the right chemical composition in which it can react with alkaline solutions properly. Meanwhile, rice husk ash contains a composition that is not appropriate to be reacted with alkaline solutions. This shows that fly ash is a suitable substitute for cement for geopolymer concrete. In the other hand, rice husk ash is not suitable for use as a substitute for cement in geopolymer concrete.